Faktor-faktor Keberhasilan Program Pelatihan Karya Tulis Ilmiah bagi Penghulu dan Penyuluh Melalui Massive Open Online Course (MOOC) PINTAR - Nahriah, Nanan (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2023)
The face-to-face training organized by Pusdiklat has yet to accommodate the maximum number of education and training participants in one period. Therefore, through an online learning platform called MOOC PINTAR, Pusdiklat presents a solution to provide opportunities for training or competency development with a broader reach. This research analyzes the factors influencing the success of training participants in Scientific Writing training for Headmasters and Extension Officers through the PINTAR MOOC. The resource person in this training is an alumni of the Indonesian Education and Religious Education and Religious Technical Personnel Training Center training participants. Data collection was carried out by distributing questionnaires and followed by interviews. The data was then analyzed using qualitative data analysis, namely the three flow models by Miles and Huberman. The research results show several factors that influence the success of training, including the training materials, learning methods, resource persons, and MOOC PINTAR platform, are suitable and have a positive and significant influence on the success of the training program, especially on indicators of participant enthusiasm in utilizing independent learning methods in MOOC PINTAR. These findings show that the Scientific Writing Training for penghulu (marriage guardian) and counselors through MOOC PINTAR at the Education and Training Center for Educational and Religious Technical Personnel of the Republic of Indonesia succeeded in developing the competence of Penghulu and Counselors in compiling Scientific Writing with a score of up to 70%. Based on the research results, the Education and Training Center is recommended to continue scientific writing training for Penghulu and Extension Officers through MOOC PINTAR.(Pelatihan yang diselenggarakan oleh Pusdiklat secara tatap muka belum mampu untuk menampung jumlah peserta pendidikan dan pelatihan secara maksimal dalam satu kurun waktu. Oleh karena itu, melalui platform online learning bernama MOOC PINTAR, Pusdiklat menghadirkan solusi guna memberikan kesempatan mengikuti pelatihan atau pengembangan kompetensi dengan jangkauan yang lebih luas. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi keberhasilan peserta pelatihan pada pelatihan Karya Tulis Ilmiah bagi Penghulu dan Penyuluh melalu MOOC PINTAR. Narasumber dalam pelatihan ini adalah alumni peserta pelatihan Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan RI. Pengumpulan data dilaksanakan dengan menyebarkan kuesioner dan dilanjutkan dengan wawancara. Data kemudian dianalisis menggunakan data analisis kualitatif, yakni three flow models oleh Miles and Huberman. Hasil penelitian menunjukkan beberapa faktor yang mempengaruhi keberhasilan pelatihan, diantaranya; materi pelatihan, metode pembelajaran, narasumber, dan platform MOOC PINTAR yang baik, dan berpengaruh secara positif dan signifikan terhadap keberhasilan program pelatihan, terutama pada indikator antusiasme peserta dalam memanfaatkan metode pembelajaran mandiri di MOOC PINTAR. Dari temuan tersebut, menunjukkan bahwa Pelatihan Karya Tulis Ilmiah bagi Penghulu dan Penyuluh melalui MOOC PINTAR pada Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan Republik Indonesia berhasil mengembangkan kompetensi Penghulu dan Penyuluh dalam menyusun Karya Tulis Ilmiah dengan skor hingga 70%. Berdasarkan hasil penelitian, disarankan agar Pusdiklat tetap memprogramkan pelatihan KTI bagi Penghulu dan Penyuluh melalui MOOC PINTAR.)